Figurative Language in Song Lyrics of the Essential Album by John Denver: Semantics Study - Novika Angel Simatupang; Ida Zuraida Supri (Universitas Cokroaminoto Palopo, 2022)
The aims of this study are 1) to analyze the types of figurative language found in “Song Lyrics of the Essential Album by John Denver”, and 2) to analyze the meanings that appeared in